Financial Wealth in Macroeconomic Dynamics - O. S. Sukharev; E. N. Voronchikhina (Финансы: теория и практика, 2022)
The article examines the financial wealth that affects macroeconomic dynamics from a comparative perspective for some countries. The purpose of the study is to identify changes in financial wealth and determine their impact on macroeconomic dynamics, taking into account the assessment of the impact of the level of social indicators — inequality and poverty, in particular, on changing the goals of economic development — growth rate, human development index. The methodology consists of empirical, structural, comparative analysis, econometric modeling, which is reduced to the construction of multiple regressions based on the Gretl 2020b software module, multiplicative models by the type of production functions. Taking into account these methods, an analysis algorithm has been developed to assess the impact of financial wealth on macroeconomic dynamics. The implementation of this algorithm made it possible to carry out a comparative analysis of the results for Russia, the G7 countries and China in terms of the influence of financial wealth on their development. The main empirical result is that financial wealth has a stronger effect on economic dynamics and social indicators of development than non-financial wealth, and is associated with the growth rate of highly developed countries. For Russia, the growth of financial wealth, albeit small, was associated with high growth rates, however, the econometric analysis revealed that financial wealth did not have a decisive influence on growth rates, reducing the human development index, unlike other countries, this affected the increase in this index. The authors conclude that the Russian economy showed the lowest sensitivity of GDP to financial wealth, but high to the Gini index, with only China and Russia having a higher sensitivity to non-financial rather than financial wealth compared to other reviewed countries. The prospect of using the results is to adjust macroeconomic policy, monetary and financial instruments, taking into account the sensitivity of target macroeconomic parameters to financial wealth, including the differentiation of policy instruments for each country.